2022
DOI: 10.1080/02640414.2023.2177027
|View full text |Cite
|
Sign up to set email alerts
|

International orienteering experts’ consensus on the definition, development, cause, impact and methods to reduce mental fatigue in orienteering: A Delphi study

Abstract: Orienteering is an outdoor activity wherein participants use a map and compass to locate control points and choose the quickest path to the next control point in a natural environment. Attentional focus, rapid decision-making, and high aerobic fitness may influence orienteering performance. Therefore, this research aimed to seek international orienteering expert consensus regarding the definition, development, causes, influences and methods to reduce mental fatigue (MF) in orienteering based on practical exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 58 publications
5
13
0
Order By: Relevance
“…(2019) have found that the individuals who frequently engage in a high self‐regulated environment perceive less stress than others. Similar to previous research, the perceived stress measured in this study was not clearly defined where there might be a variation in the interpretation and definition of stress between participants (Lam, Sproule, Turner, & Phillips, 2023; Russell, Jenkins, Halson, Juliff, et al., 2022). For a more accurate measurement of stress, future research should specify the type of stress, for example, cognitive stress instead of a general stress in order to further explore any potential interplay between stress and MF.…”
Section: Discussionsupporting
confidence: 54%
See 4 more Smart Citations
“…(2019) have found that the individuals who frequently engage in a high self‐regulated environment perceive less stress than others. Similar to previous research, the perceived stress measured in this study was not clearly defined where there might be a variation in the interpretation and definition of stress between participants (Lam, Sproule, Turner, & Phillips, 2023; Russell, Jenkins, Halson, Juliff, et al., 2022). For a more accurate measurement of stress, future research should specify the type of stress, for example, cognitive stress instead of a general stress in order to further explore any potential interplay between stress and MF.…”
Section: Discussionsupporting
confidence: 54%
“…Therefore, this study cannot validate whether orienteers would experience the similar delay in recovery observed in this study during a typical preseason training week or camp. Importantly, although previous research has reported that routine school/university education and non‐orienteering challenges might also affect perceived MF and psychological responses negatively (Lam, Sproule, Turner, Murgatroyd, et al., 2023; Thompson et al., 2020), the influence of education on delayed recovery in 24POST and 48POST should be limited as the participants in this study were full‐time students and were on spring break. To address this limitation, future research could implement a longitudinal research design to determine the day‐to‐day changes and observe if a normal training week would generate a similar result to that of a training camp.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations